PENGARUH PENGGUNAAN QUICK RESPONSE INDONESIA STANDARD (QRIS) DAN CASH TERHADAP KEPUTUSAN BELANJA DI ALFAMART GAMBUT KALIMANTAN SELATAN - Aisyah, Lisda (Al-Ujrah | Jurnal Ekonomi Syariah, 2025)
This study aims to examine the effect of using QRIS and Cash on a consumer's shopping decision. A total of 43 respondents were involved as research samples selected using the incidental sampling method. The data were analyzed using quantitative methods including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing through t and f tests and the coefficient of determination test (R2 Test). Data that meets the criteria for validity, reliability and classical assumption tests are processed using SPSS software, obtaining the following regression equation: Y = -2.325 + 0.531 X1 + 0.436 X2 with variable use of QRIS (X1), Cash (X2) and Shopping Decisions (Y). the results of hypothesis testing show that if the use of QRIS and Cash has a positive and significant effect on shopping decisions. The coefficient of determination (R2) of 0.519 indicates that 51.9% of shopping decisions at Alfamart are influenced by the variables studied, while the remaining 48.1% is caused by other variables not analyzed in this study.